The Rise and Fall of Priming: How Visual Exposure Shapes Cortical Representations of Objects - Zago, Laure (2005)
How does the amount of time for which we see an object influence the nature and content of its cortical representation? To address this question, we varied the duration of initial exposure to visual objects and then measured functional magnetic resonance imaging (fMRI) signal and behavioral performance during a subsequent repeated presentation of these objects. We report a novel ‘rise-and-fall’ pattern relating exposure duration and the corresponding magnitude of fMRI cortical signal. Compared with novel objects, repeated objects elicited maximal cortical response reduction when initially presented for 250 ms. Counter-intuitively, initially seeing an object for a longer duration significantly reduced the magnitude of this effect. This ‘rise-and-fall’ pattern was also evident for the corresponding behavioral priming. To account for these findings, we propose that the earlier interval of an exposure to a visual stimulus results in a fine-tuning of the cortical response, while additional exposure promotes selection of a subset of key features for continued representation. These two independent mechanisms complement each other in shaping object representations with experience.